2022
DOI: 10.21037/atm-21-4322
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and prognosis for patients with sarcomatoid hepatocellular carcinoma

Abstract: Background: Characterized by spindle cell composition in hepatocellular carcinoma tumor, sarcomatoid hepatocellular carcinoma (SHC) is a rare malignant with poor prognosis. In this study, we aimed to evaluate the clinical and pathological features of SHC and establish a nomogram that can predict long-term outcomes of the disease.Methods: We retrospectively analyzed 63 patients who were diagnosed with SHC between October 2007and November 2016 and used immunohistochemistry (IHC) to assessed various markers in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Several studies indicate radical surgical resection to be the most effective treatment for SHC ( 15 , 24 ). A retrospective study that included 63 cases of resected SHC showed the median overall and recurrence-free survival duration to be 23.2 and 8.4 months, respectively; the 1-, 2-, and 3-year overall survival rates were 59.0%, 45.4%, and 34.4%, respectively, and the 1-, 2-, and 3-year recurrence-free survival rates were 36.3%, 26.1%, and 22.4%, respectively ( 25 ). Morisue et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate radical surgical resection to be the most effective treatment for SHC ( 15 , 24 ). A retrospective study that included 63 cases of resected SHC showed the median overall and recurrence-free survival duration to be 23.2 and 8.4 months, respectively; the 1-, 2-, and 3-year overall survival rates were 59.0%, 45.4%, and 34.4%, respectively, and the 1-, 2-, and 3-year recurrence-free survival rates were 36.3%, 26.1%, and 22.4%, respectively ( 25 ). Morisue et al.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the aggressive nature of SHC surpasses that of conventional HCC, subsequently leading to an inferior prognosis. [11,12] In this case, our approach encompassed hepatectomy coupled with ultrasound-guided radiofrequency ablation for HCC. Intraoperative ultrasound localization was employed for accurate tumor identification, followed by postoperative hepatic artery embolization to facilitate meticulous tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…Even if SHC is highly malignant, the pathogenesis of the sarcomatoid transformation remains unknown. The potential risk factors proposed by several previous studies were transarterial embolization, radiofrequency ablation and chronic biliary inflammatory stress [4]. Nevertheless, some individuals still develop SHC even if they do not undergo anticancer therapy [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SHC varies from 1.8-2.0% in surgically resected cases [2,3]. Previous studies reported that SHC was more likely to occur in patients who received repeated anticancer therapies, including transarterial embolization and radiofrequency ablation [3,4]. Hepatitis, one of the causative factors of hepatocellular carcinoma (HCC), is also considered a risk factor for SHC [5].…”
Section: Introductionmentioning
confidence: 99%